posted by .

ln x^2(x+1)/x+2

Write in terms of ln(x), ln(x+1), and ln(x+2)

is the correct steps this?
lnx^2 + ln(x+1) - ln(x+2) = 2lnx + ln(x+1) - ln(x+2)

  • Math -

    Good job.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    The volume of a solid is given by V=pi x^2(lnx)^2. what is the approximate change in the volume when x is increased from 2.718 to 3.000?
  2. Calculus

    Solve for x: lnx^3 - 2lnx = 1 Please try and show how you got the answer best as you can thank you :)
  3. calculus

    1. e^ln3 - 2lnx 2. 2(lnx)^2 + lnx - 1 =0 3. d/dx (e^x . e^e^x)
  4. L'Hopital's rule

    Find lim x->1+ of [(1/(x-1))-(1/lnx)]. Here is my work... =(lnx-(x-1)) / ((x-1)(lnx)) =(lnx-1) / (lnx+ (x+1)/x) This becomes(1/x) / ((1/x)+(1/x^2)) which becomes 1/ (1/x^2) This equals 1/2. I understand the answer has to be -1/2, …
  5. Calculus 1

    Find the derivative of y with respect to x. y=(x^6/6)(lnx)-(x^6/36) So far this is what I've gotten: y=(x^6/6)(lnx)-(x^6/36) y=(1/6)x^6(lnx)-(1/36)x^6 y'=(1/6)x^5(1/x)+lnx(x^5)-(1/6)x^5 What do I do now?
  6. calculus

    sorry to ask a second question so soon, but i'm just not getting this one. if f(x)= 3x lnx, then f'(x)=?
  7. Algebra II

    Is this correct? Solve: 2lnx-2=0 2lnx=2 Lnex=1 E^1=x
  8. math: pre-calculus

    Let u=ln and v=ln y. Write the expression ln(5√(x3√y)) in terms of u and v. for example, lnx^3y = lnx^3+lny = 3lnx+lny = 3u+v
  9. math: pre-calculus

    Let u=lnx and v=lny. Write the expression ln3√x/2y in terms of u and v. For example, lnx^3y=lnx^3+lny=3lnx +lny= 3u+v.
  10. Pre-Calculus

    Assume that x, y, and z are positive numbers. Use the properties of logarithms to write the expression 2lnx - 6lny + 1/3ln e^12 as a simplified logarithm. Is this 2lnx - 6lny + 4, or can it be simplified further?

More Similar Questions